Effect of examination stress on some biochemical indices in Tikrit College students - Hashim Abdul-Sattar J. Al-Bajalani (International Journal of Medicine and Health, 2024)
This study aimed to investigate the physiological impact of academic stress, particularly examination stress, on biochemical indices among college students at the University of Tikrit. A total of 60 healthy students (30 in an experimental group and 30 in a control group) aged 19-21 years participated in this cross-sectional study. Salivary samples were collected during pre-examination and post-examination periods to measure levels of cortisol, malondialdehyde (MDA), glucose, and total antioxidant capacity (TAC). The results indicated significant increases in cortisol, MDA, and glucose levels in the pre-examination period compared to the post-examination period, suggesting heightened stress responses. Conversely, TAC levels were significantly higher in the post-examination period, indicating a potential recovery or response to oxidative stress. The findings support the hypothesis that academic examinations can induce significant physiological stress in students, reflected by changes in salivary biochemical markers. These stress responses may influence overall student health and academic performance, suggesting the need for strategies to manage stress among students during examinations.